Journalistic formats and genres based on the use of WhatsApp in community journalism - Gómez-Monsalve, Wilmar-Daniel; Trejos-Gil, Carlos-Andrés; Bulla-Castro, Cristian-Mauricio (Infonomy, 2024)
WhatsApp is one of the most popular mobile applications in the world. Nearly 2,000 million active users interact daily through this instant messaging application. This research sought to analyze the use and the most frequented journalistic formats on WhatsApp in three community media outlets in Antioquia - Colombia, such as: Eje Central and Emisora La Buena 95.4 FM in communes three and four of the municipality of Bello and Mi Comuna Dos, in commune two, of the city of Medellin. Through a qualitative methodology with instruments such as interviews, surveys and observations, it was understood, in the selected cases, the different dynamics in front of the categories of the informative contents that are broadcast, the community interests about them and the recurrent platforms to distribute information community.
Keywords: Citizen journalism; Journalistic formats; Journalistic genres; Prosumers; Audiences; Participation; ICT; WhatsApp; Social networks; UGC